(3GdebOeI GdSGdeI aj Nha GdNGJeIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG Edi GdUQGW GdeSJbje CeG HYO ajbhd Cf Gddg SHMGfg bGd (B" (3aCefhG ecQG Gddg adG jCef ecQ Gddg EdG Gdbhe GdNGSQhf (B" s
(3BNQgG (B:s
(3hbQ YjffG HcTa ebGe Mb Gdjbjf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HMhGTjgG TQhMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs